COESITE (SIO2) AS AN EXTREME CASE OF SUPERHEATED CRYSTAL: AN X-RAY DIFFRACTION STUDY UP TO 1776 K - Bourova E.; Richet P.; Petitet J.-P. (My University, 2006)
The dense SiO2 polymorph coesite has been investigated by X-ray powder diffraction from room temperature up to 1776 K. No phase transition has been detected in this temperature interval. Thermal expansion shows little anisotropy and remains very small since the volume increases by only 1.6% between 300 and 1776 K. As indicated by theoretical simulations, the small dilation results from limited rotations of SiO4 tetrahedra and also from slight expansion of Si-O bonds. In addition, the results demonstrate that coesite can be kept 900° above its metastable congruent temperature of fusion which is about 875 K. Comparisons with measurements made under the same conditions for quartz and cristobalite indicate that, for SiO2 polymorphs with 4-fold coordinated Si, crystal structure exerts a smaller influence than melt viscosity on the extent of superheating. © 2006 Elsevier B.V. All rights reserved.
Keywords: COESITE; SUPERHEATING; THERMAL EXPANSION